ANP and ELECTRE Methods for Determine New Student Admissions - Kustiyahningsih, Yeni; Sophan, Mochammad Kautsar; Ikhsan, Achmad Faris (Universitas Muhammadiyah Malang, 2020)
Higher Education is a level of education after High School which selects new students based on achievement, report cards, and tests. Admission selection was based on report cards. Number of indicators and who register make it difficult for determine which students are accepted in education. Multi criteria Group Decision Making (MCGDM) is decision-making method to determine best alternative from a number of alternatives based on certain criteria. In this study, MCGDM used is Analytic Network Process (ANP) and Elimination and Choice Expression Reality (ELECTRE). ANP model is a development of AHP and requires linkages between criteria using a network. ELECTRE is method based concept of ranking through pairwise comparisons between alternatives on the appropriate criteria. Contribution is integration ANP and ELECTRE methods based on group, by determining decisions based on consistency ratio. The results of testing level consistency ratio, group-based ANP-ELECTRE can be applied to assessment selection at Electrical Engineering with highest accuracy of 86.36%.